Current account sustainability in selected Asia countries : Indonesia, Korea and Thailand - Lee, Zi Yuen (2008)
This final year research project examines the current account sustainability of selected Asian countries, namely; Indonesia, Thailand and Korea . The three countries suffered from current account deficits for most of the 1990s and the current accounts only posted positive figures in the late 1990s due to the Asian Financial Crisis.